Speaking Skills Learning Based on Politeness for Conflict Resolution Education in Higher Education - Muhammad Saleh; Sultan Sultan (Seminar Nasional LP2M UNM, 2019)
Abstract. Speaking skills are an important aspect for every individual to develop themselves socially and professionally. From the social side, speaking skills will help individuals establish harmonious relationships with other individuals/ groups for a variety of interests. From a professional perspective, speaking skills as part of communication skills are key factors that support career success. Inter-student conflict is one of the social problems facing universities today, mainly in South Sulawesi. Data shows that during 2003–2011 there were 60 student conflicts. Politeness values that grow from cultural roots can be used to build mutual respect, respect, and tolerance between students through lectures on speaking skills. Conflict resolution is one aspect that can be instilled through learning activities. From various approaches to conflict resolution education, the most essential goal is to instill awareness in students of the importance of establishing humanitarian interactions and relations and actively involving them in resolving conflicts. To prevent conflict, everyone should understand the culture and ways of communicating that apply in certain community groups. Learning language skills, especially speaking skills, is one of the media for planting anti-conflict values. Through learning politeness-based speaking skills, students can develop themselves to communicate politely and with dignity to avoid conflict.